Hubungan di antara faktor ergonomik dengan tekanan pekerjaan dalam sektor penyelidikan dan pembangunan: kajian dalam kalangan pekerja di MIMOS Berhad - Mohamad Zulfadli, Hasni (2018)
This study aims to look at the relationship between ergonomic factors and job stress among workers at MIMOS Berhad. In addition, this study also examines the ergonomic factors that most influence job stress. This study also aims to identify whether there is a significant relationship between ergonomic factors and job stress. The ergonomic factors studied are in terms of body posture, health, workstation, workstation environment and working hours. A total of 168 respondents were involved in this study. A set of questionnaires consisted of three sections totalling 61 questions used to collect data. The data obtained were analyzed using Statistical Packages for Social Sciences (SPSS) version 23.0. For data analysis, the frequency distribution method and percentage have been used to analyze the demographic factors of the respondents. Mean score method and standard deviation to determine the central tendency of feedback and the degree of influence of ergonomic factors on job stress. Next, to identify the relationship between ergonomic factors and job stress, the Pearson Correlation test has been used. The findings show that ergonomic factors (body posture, health and workplace environment) have a significant relationship with job stress. While ergonomic factors (workstations and working hours) have no significant relationship with job stress. While multiple regression analysis is used to identify ergonomic factors which most affect job stress found that health factors are the most factor that influences job stress. Summarizes this study overall, there is a significant relationship between ergonomic factors and job stress.